2016
DOI: 10.1016/j.psyneuen.2016.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Histories of abuse predict stronger within-person covariation of ovarian steroids and mood symptoms in women with menstrually related mood disorder

Abstract: Objective Individual differences in sensitivity to cyclical changes in ovarian steroids estradiol (E2) and progesterone (P4) have been implicated in the pathophysiology of menstrually related mood disorder (MRMD). However, no prospective studies have investigated psychosocial risk factors for sensitivity to hormone effects on mood in MRMD. Using a repeated measures approach and multilevel models, we tested the hypothesis that a history of abuse provides a context in which within-person elevations of E2 and P4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Individuals affected by PMDD are therefore ascribed hormone sensitivity [59]. Previous research traced inter-individual differences in hormone sensitivity (indicated by the emergence of PMDD symptoms) back to, for example, traumatic experiences in the woman's biography [60][61][62][63]. In the light of the present work, the question is whether intra-individual fluctuations of HRV across the cycle may be a physiological marker of hormone sensitivity (comparable to traumatic experiences as a biographical marker).…”
Section: Implications For Future Researchmentioning
confidence: 75%
“…Individuals affected by PMDD are therefore ascribed hormone sensitivity [59]. Previous research traced inter-individual differences in hormone sensitivity (indicated by the emergence of PMDD symptoms) back to, for example, traumatic experiences in the woman's biography [60][61][62][63]. In the light of the present work, the question is whether intra-individual fluctuations of HRV across the cycle may be a physiological marker of hormone sensitivity (comparable to traumatic experiences as a biographical marker).…”
Section: Implications For Future Researchmentioning
confidence: 75%
“…Expert diagnoses (coauthor DR) of MRMD made prior to the development of the C-PASS (on the basis of identical data) were available for the majority of our sample (193 women; 96.5%). Because the DRSP summed total score demonstrates inadequate reliability of change 17 , descriptive statistics for single items are considered.…”
Section: Methodsmentioning
confidence: 99%
“…However, another study in a sample of patients with prospectively-diagnosed PMDD found that the strength of the daily link between progesterone levels and symptoms was stronger in patients with histories of trauma exposure, suggesting a possible influence of trauma on the severity (rather than the occurrence) of luteal phase symptoms in PMDD (Eisenlohr-Moul et al, 2016). In addition to historical trauma exposure, current stress may increase risk for PMDD symptoms.…”
Section: Premenstrual Disorders 10mentioning
confidence: 98%